2019
DOI: 10.1186/s13023-019-1202-6
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between results of meta-analyses from case reports and clinical studies, regarding efficacy and safety of idursulfase therapy in patients with mucopolysaccharidosis type II (MPS-II). A new tool for evidence-based medicine in rare diseases

Abstract: BackgroundA preliminary exploratory study shows solid agreement between the results of case reports and clinical study meta-analyses in mucopolysaccharidosis Type I (MPS-I) adult patients. The aim of the present study is to confirm previous results in another patient population, suffering from mucopolysaccharidosis Type II (MPS-II).MethodsA systematic review and meta-analysis of case reports published by April 2018 was conducted for MPS-II patients treated with enzyme replacement therapy (ERT). The study is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…Another limitation was that results from case series and case-control studies were used for prevalence estimations. However, previous studies XXX have suggested and used case reports/ series in meta-analyses to facilitate the decision making process when the evidence was limited PLOS ONE or a relatively rare or neglected disease was assessed [54][55][56][57][58][59]. In addition, the most recently published meta-analysis of 44 case series reported the 25-year pooled survival of hip replacements [60].…”
Section: Limitationsmentioning
confidence: 99%
“…Another limitation was that results from case series and case-control studies were used for prevalence estimations. However, previous studies XXX have suggested and used case reports/ series in meta-analyses to facilitate the decision making process when the evidence was limited PLOS ONE or a relatively rare or neglected disease was assessed [54][55][56][57][58][59]. In addition, the most recently published meta-analysis of 44 case series reported the 25-year pooled survival of hip replacements [60].…”
Section: Limitationsmentioning
confidence: 99%
“…Due to the rarity of aceruloplasminemia, randomized controlled study designs are not feasible to explore clinical outcomes of iron chelation therapy. The value of aggregated case reports has recently been highlighted as an alternative means of systematically deriving evidence from the literature in rare diseases [11,12]. However, the rich source of information embedded in published case reports and case series has not yet been quantitatively investigated in such manner for aceruloplasminemia.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rarity of this tumor, the knowledge is mainly based on case reports or case series resulting in limited statistical signi cance concerning epidemiology, demographics, clinical characteristics and treatment e cacy [1,3,9]. Nevertheless, case report meta-analyses might help improving the clinical practice in the context of rare diseases and provide more information to guide clinicians and surgeons to appropriate treatment [21]. Here we summarized case series and case reports concerning LGMS of the extremities in a quantitative manner.…”
Section: Discussionmentioning
confidence: 99%